Synthesis and in vitro activities of ferrocenic aminohydroxynaphthoquinones against Toxoplasma gondii and Plasmodium falciparum - Apiwat Baramee (2018)
Fourteen ferrocenyl aminohydroxynaphthoquinones, analogues of atovaquone, were synthesized from the hydroxynaphthoquinone core. These novel atovaquone derivatives were tested for their in vitro activity against two apicomplexan parasites of medical importance, Toxoplasma gondii and Plasmodium falciparum, including resistant strains to atovaquone (T. gondii) and chloroquine (P. falciparum). Three of these ferrocenic atovaquone derivatives composed of the hydroxynaphthoquinone core plus an amino-ferrocenic group and an aliphatic chain with 6-8 carbon atoms were found to be significantly active against T. gondii. Moreover, these novel compounds were also effective against the atovaquone-resistant strain of T. gondii (AtoR). © 2005 Elsevier Ltd. All rights reserved.